Base de dados Paisagem e Povoamento (diocese de Braga, Séculos IX-XI) - André Evangelista Marques (2013)
The database "Paisagem e Povoamento (diocese de Braga, Séculos IX-XI)" has been built as part of the research conducting to the PhD thesis "Landscape and settlement: between documentary representation and the physical realization of space in the territory of Braga's diocese (9th-11th centuries). Methodological essay." by André Evangelista Marques, PhD in History by the Humanities Faculty of the University of Porto, 2012 (http://hdl.handle.net/10216/67231). The abstract of the thesis follows.Initially conceived as yet another regional study on the social organization of space, this dissertation came to focus specifically on the physical morphology of the several spatial units underpinning the landscape and settlement organization in the territory of Braga's diocese from c. 875 through 1100. This became, in fact, a dissertation concerned not so much with a thorough empirical account, within precise time and space boundaries, but mostly with putting forward a method of spatial analysis (to be more specific, of the several types of units which build space up in the documentary discourse), particularly designed for early medieval charter evidence. The programme of this dissertation thus stands out due to a double instrumental purpose: (i) to propose such a method; and (ii), as its primary stage, to develop a reflection (applied to a particular documentary corpus) on the possibilities of written evidence regarding the physical realization of space. Both aims pave the way to the dissertation's two parts: the first is dedicated to the theoretical grounding and description of the proposed method and the second to the issues which arise from the documentary representation of space, chief among which is the analysis of the lexicon used in the selected corpus to classify morphologically the spatial units referred.The database management system that have been used is MS Access 2010, file format Access 2000. The database "Paisagem e Povoamento (diocese de Braga, Séculos IX-XI)" (contents in Portuguese) is available for researchers to verify the thesis results and to use in future research.